Toward a theoretical framework for ethical decision making of street-level bureaucracy: existing models reconsidered - Loyens, Kim; Maesschalck, Jeroen (2010)
Much research has been done on the way in which individuals in organizations deal with their discretion. This article focuses on the literature on street-level bureaucracy and the literature on ethnical decision making. Despite their shared attempt to explain individual behavior and decision making, these research traditions have been developed quite independently. Moreover, although they both list relevant influencing factors, they do not succeed entirely in clarifying how and under which circumstances these factors have an impact on individual behavior and decision making. This article attempts to substantiate how the concept of social mechanism could help to open the black box of causation. - Reproduced.
Keywords: Bureaucracy; Civil service; Decision making